Insights into the innate immunome of actiniarians using a comparative genomic approach. (December 2016) - van der Burg, Chloé; Prentis, Peter; Surm, Joachim; Pavasovic, Ana
Abstract Background Innate immune genes tend to be highly conserved in metazoans, even in early divergent lineages such as Cnidaria (jellyfish, corals, hydroids and sea anemones) and Porifera (sponges). However, constant and diverse selection pressures on the immune system have driven the expansion and diversification of different immune gene families in a lineage-specific manner. To investigate how the innate immune system has evolved in a subset of sea anemone species (Order: Actiniaria), we performed a comprehensive and comparative study using 10 newly sequenced transcriptomes, as well as three publically available transcriptomes, to identify the origins, expansions and contractions of candidate and novel immune gene families. Results We characterised five conserved genes and gene families, as well as multiple novel innate immune genes, including the newly recognised putative pattern recognition receptor CniFL. Single copies ofTLR, MyD88 andNF-κB were found in most species, and several copies ofIL-1R- like, NLR andCniFL were found in almost all species. Multiple novel immune genes were identified with domain architectures including the Toll/interleukin-1 receptor (TIR) homology domain, which is well documented as functioning in protein-protein interactions and signal transduction in immune pathways. We hypothesise that these genes may interact as novel proteins in immune pathways of cnidarian species. Novelty in the actiniarian immunome is not restricted to only TIR-domain-containing proteins, as we identify a subset of NLRs which have undergone neofunctionalisation and contain 3–5 N-terminal transmembrane domains, which have so far only been identified in two anthozoan species. Conclusions This research has significance in understanding the evolution and origin of the core eumetazoan gene set, including how novel innate immune genes evolve. For example, the evolution of transmembrane domain containing NLRs indicates that these NLRs may be membrane-bound, while all other metazoan and plant NLRs are exclusively cytosolic receptors. This is one example of how species without an adaptive immune system may evolve innovative solutions to detect pathogens or interact with native microbiota. Overall, these results provide an insight into the evolution of the innate immune system, and show that early divergent lineages, such as actiniarians, have a diverse repertoire of conserved and novel innate immune genes.